Pendidikan Kesehatan Tentang JKN Mobile Dalam Upaya Pemeliharaan Kesehatan Lansia - Fauziah, Ani (LPPM Politeknik Piksi Ganesha, 2024)
In this digital era, there are still some people who do not understand the use of Mobile (JKN). Especially the elderly who have sophisticated smartphones. JKN mobile is one of the health history screenings compiled by BPJS Kesehatan which is a screening made with the aim of finding out whether JKN KIS participants have a risk of 4 NCDs, namely: hypertension, Diabetes Mellitus, chronic kidney disease, coronary heart disease which is useful for maintaining the health of the elderly. In order to increase knowledge, understanding of the elderly about JKN mobile in health maintenance efforts, health education is carried out. The result of this activity is an increase in clear knowledge for the elderly about JKN mobile through counseling using leaflets